Investigation of the Efficiency of Drying Conditions for Essential Oil Produc-tion from Aromatic Plants - Özgüven, Menşure; Gülseren, Gülcihan; Müller, Joachim (UI Scholars Hub, 2019)
The active components of aromatic medicinal plants have extensive applications in many disciplines. These essential oil components are extracted from medicinal plants, and the removal of water is a critical step of this process. Different drying methods have been developed to produce high-quality and high-quantity products. In this study, different drying methods were investigated with respect to their effects on herbal oil content. Two distinct aromatic plants, i.e., Thymus vulgaris L. and Mentha citrata Ehrh., were selected for physical and chemical analyses. To understand and elucidate the importance of method selection, the relationship between parameters, such as moisture content and drying time, was correlated with essential oil recovery and active ingredient levels. Recently, solar tunnel drying emerged as a novel technique with various advantages. We implemented this technique to analyze its effectiveness on the removal of water from different plant species. Our recent findings from essential oil and humidity content analyses showed that T. vulgaris L. is a more suitable candidate for the solar tunnel drying process than M. citrata Ehrh. Solar tunnel and oven drying have been determined to be the best dehumidification methods for both plant species. The differences between these drying methods were not significant for M. citrata Ehrh. By contrast, these drying methods can cause significant variations in the oil content of T. vulgaris L. Essential oil compositions have also been observed to be dependent on the drying conditions. These results indicated the significance of method selection in obtaining products with high yield.